Control de inventarios en el Comercial Don Julio del cantón Montalvo - Gallegos Manobanda, Yessica Johanna (2020)
Inventory control is one of the very effective and important management systems within commercial companies, whether they are small or large, because many of the activities depend on this procedure to efficiently comply with each commercial process in which it operates, and that keep in constant knowledge as is the situation within it, in the event that this method is not registered with the techniques and strategies necessary for the proper functioning of commercial operations, conflicts may arise that are not detected in time and would cause decrease in profitability in the company. The work environment within companies is essential to generate an adequate internal and external environment because it helps to reveal what people will do within an organization to be able to describe the behavior of each person whether or not they have the skills and ability to deal with clients and understand them without causing conflicts to function with greater efficiency and productivity, bringing with it success for the company and for all the people who work in it. This case analysis was carried out with the main purpose of identifying the difficulties in the management of merchandise in terms of the coordination and control of the inputs and outputs thereof; Through an investigation of the Commercial "DON JULIO" several inconveniences were observed such as; mismanagement of inventory, absence of its owner, closure of the premises due to merchandise in poor condition, an inappropriate work environment and with them they are generating low profitability.